Usborne Phonics Readers Mouse Moves House - Phil Roxbee Cox (London, United Kingdom Usborne Publishing Ltd, 2006)
This amusing series of early reading books uses phonics repetition to help children learn to read. A phonic breakdown of the text is given by expert Marylynne Grant to help parents and teachers.
Keywords: Read Aloud -- Read Aloud